(3GdYbe YfO GdQLGd hGdfSGA (B:s (3CSHGHg hYdGLg (B/s - (3aGNhQj, SHjQhs ((3HjQhJ (B:s (3OGQ GdYde ddedGjjf,s, 1984)
(3GdYbe YfO GdQLGd(B-(3GdLgGR GdJfGSdj YfO GdQLd hhXjaJg(B-(3CSHGH GdYbe YfO GdQLGd(B-(3GdYbe GdfSHj(B-(3aMU GdQLd GdYbje(B-(3Gdefj(B-(3ehGUaGJ GdSGFd Gdefhj GdLjO(B-(3WQb GdMUhd Ydi Gdefj haMUg(B-(3ehGUaGJ GdSGFd Gdefhj YfO GdQLd GdYbje(B-(3GdaMhU GdeNHQjI aj Ybe GdQLGd(B-(3YdGL GdYbe YfO GdQLd(B-(3GdYbe YfO GdfSGA(B-(3CYVGA GdeQCI GdJfGSdjI(B-(3CSHGH GdYbe YfO GdeQCI(B-(3aMU GdeQCI GdeUGHI HGdYbe(B-(3GdaMU GdWHj GdYGe(B-(3JTNjU GdYbe GdfGLe Yf GfSOGO GdfajQjf(B-(3YdGL GdYbe YfO GdeQCI(B-(3eYGdLI GdYbe HhGSWI GdLQGMI(B-(3eYGdLI GdYbe HhGSWI JdbjM GdHhjVI aj CfHhH GdeNJHQ(B-(3GdJdbjM GdGUWfGYj(B-(3CSFdI hCLhHI(B.s
Keywords: (3Ybe GdPchQs; (3Ybe GdEfGKs; (3GdCeQGV GdJfGSdjI GdPcQjIs; (3GdCeQGV GdJfGSdjI GdCfKhjIs